The lingual sulcus release technique for excision of tongue cancer with trismus. Issue 12 (December 2020) - Rao, V.; Sinha, P.; Subash, A.; Thakur, S.
Abstract: Operable oral tongue cancers are managed best with surgery followed by adjuvant therapy as and when indicated. The only factor that affects the prognosis, and is under the control of a surgeon, is the tumour margin. Often in cases with trismus, which is prevalent in tobacco and areca nut users, obtaining a clear margin intraorally can be challenging. Approaches described until now to obtain clear margins in these cases have a great impact on the postoperative recovery and morbidity. In our experience, lingual sulcus release is a safe and reproducible technique for these cases. The transcervically elevated lingual sulcus provides an additional layer of safe margin for the management of squamous cell tongue carcinoma with trismus.